2020
DOI: 10.1158/1940-6207.capr-20-0411
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Whole Population BRCA Genetic Screening for Cancer Prevention in Israel

Abstract: With the growing technical ease and reduction in genetic screening costs, whole population BRCA screening may be a feasible option. Our objective was to investigate the cost effectiveness of whole population screening for BRCA mutations in Israel, for varying degrees of BRCA carrier state. Lifetime costs of whole female population screening for BRCA mutation carrier state versus nonscreening were compared using a Markovian process decision analysis model. Model parameters including ovarian and breast cancer ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…These rates of germline BRCA1 and BRCA2 pathogenic variants in an unselected Jewish population and particularly the yield of 2.6% in AJs are well established 20,21 and further strengthen the rationale for including targeted BRCA1 / BRCA2 genotyping for all Jewish women, regardless of ethnicity or a family history of cancer 21,22 . Population‐based genotyping in Israel was recently reported to be cost‐effective, 23 as previously shown in the United States and the United Kingdom 21,22 …”
Section: Discussionmentioning
confidence: 52%
“…These rates of germline BRCA1 and BRCA2 pathogenic variants in an unselected Jewish population and particularly the yield of 2.6% in AJs are well established 20,21 and further strengthen the rationale for including targeted BRCA1 / BRCA2 genotyping for all Jewish women, regardless of ethnicity or a family history of cancer 21,22 . Population‐based genotyping in Israel was recently reported to be cost‐effective, 23 as previously shown in the United States and the United Kingdom 21,22 …”
Section: Discussionmentioning
confidence: 52%
“…This is by no means limited to DNA samples from neonatal blood spots. Several studies have investigated the cost-effectiveness of population screening for adult CPSs [18][19][20][21][22] . One such study 22 , investigating the impact of PPS on universal adult screening for BRCA1/2 and MMR genes, found it to be conservatively cost-effective even at PPS exceeding $1000.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence had shown that relying on personal and family history may not be sufficient to determine the risk for BRCA1/2 variants ( 20 ). Population BRCA screening is considered the trend in the near future ( 124 , 125 ). Thus, a growing number of healthy individuals harboring pathogenic mutations can be identified for cancer prevention.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%